2008
DOI: 10.1189/jlb.0608374
|View full text |Cite
|
Sign up to set email alerts
|

LPS activation is required for migratory activity and antigen presentation by tolerogenic dendritic cells

Abstract: Autoimmune pathologies are caused by a breakdown in self-tolerance. Tolerogenic dendritic cells (tolDC) are a promising immunotherapeutic tool for restoring self-tolerance in an antigen-specific manner. Studies about tolDC have focused largely on generating stable maturation-resistant DC, but few have fully addressed questions about the antigen-presenting and migratory capacities of these cells, prerequisites for successful immunotherapy. Here, we investigated whether human tolDC, generated with dexamethasone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
110
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(128 citation statements)
references
References 60 publications
13
110
0
5
Order By: Relevance
“…Interestingly, human tolDC, generated with dexamethasone and the active form of vitamin D3, were shown not only to maintain their tolerogenic function upon activation with maturation stimuli (LPS) but were superior in terms of their migratory activity toward CCL19 (confirmed in our report72) and had enhanced antigen‐presenting ability 23. Citrullinated‐peptide‐pulsed tolDC have also been reported to be safe and effective in a Phase 1 clinical study in patients with rheumatoid arthritis 13.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Interestingly, human tolDC, generated with dexamethasone and the active form of vitamin D3, were shown not only to maintain their tolerogenic function upon activation with maturation stimuli (LPS) but were superior in terms of their migratory activity toward CCL19 (confirmed in our report72) and had enhanced antigen‐presenting ability 23. Citrullinated‐peptide‐pulsed tolDC have also been reported to be safe and effective in a Phase 1 clinical study in patients with rheumatoid arthritis 13.…”
Section: Discussionsupporting
confidence: 51%
“…However, phenotypic characterization alone is insufficient to determine whether DC will induce tolerance or immunity 21, 22. In addition, it has been suggested that irrespective of the desired therapeutic outcome (induction of tolerance for prevention of autoimmune disease or immunity for treatment of cancer) DC activation is essential for the effectiveness of immunotherapy as activated DC preferentially migrate from the peripheral tissues into the draining lymph nodes where antigen‐specific interaction with T cells occurs 23, 24, 25…”
Section: Introductionmentioning
confidence: 99%
“…Notably, activation through TLR4 is essential for DCs to acquire a functional migratory capacity. Therefore, it is conceivable that Ctr-mDCs would have a greater ability to migrate in vivo, because treatment with 1,25(OH) 2 D 3 counteracts several aspects of DC activation/maturation following exposure to such TLR stimuli (55). Strikingly, we show that NOD-derived 1,25D 3 -mDCs exhibited increased functional capacity to migrate to the pancreas and liver of recipient adult NOD compared with Ctr-mDCs.…”
Section: Discussionmentioning
confidence: 49%
“…Treatment of DCs with 1␣,25-dihydroxyvitamin D 3 (vitamin D 3 ) in combination with dexamethasone has been shown to synergistically inhibit lipopolysaccharide (LPS)-induced maturation of DCs (24). Previously, we used these immunosuppressive drugs to generate human tolerogenic DCs with potent immunoregulatory function in vitro (25,26). An important outstanding question is, however, whether these pharmacologically modified tolerogenic DCs can inhibit pathogenic IL-17-mediated responses in vivo, and whether they will be effective at reducing the progression and severity of arthritis when administered after disease onset.…”
Section: Conclusion Treatment With Type II Collagenpulsed Tolerogenimentioning
confidence: 99%